(untitled) (The Review of Diabetic Studies, 2024)
The empowerment of women during pregnancy and childbirth is crucial for improving maternal and neonatal health outcomes. This review article examines the significant role of midwives in enhancing these outcomes through comprehensive, womancentered care. Midwives, as trained healthcare professionals specializing in normal pregnancy and childbirth, provide not only clinical support but also emotional and psychological guidance, fostering a sense of autonomy among women. Research indicates that midwifery care is associated with lower rates of interventions such as cesarean sections and instrumental deliveries, as well as reduced maternal mortality. Additionally, midwives contribute to improved mental health outcomes for mothers by offering continuous support and education throughout the perinatal period. The impact of midwives extends to neonatal health, with evidence suggesting that midwifery-led care is linked to lower rates of preterm birth and low birth weight, thereby enhancing overall neonatal well-being. Furthermore, midwives play a vital role in promoting breastfeeding, which is essential for infant health, by providing guidance and addressing challenges that mothers may face. Culturally competent care is another critical aspect of midwifery practice, as it ensures that care is respectful and responsive to the diverse backgrounds of women, ultimately leading to better health outcomes. Despite the positive contributions of midwives, systemic barriers such as regulatory challenges, workforce shortages, and a lack of recognition hinder their ability to provide optimal care. This article advocates for the integration of midwifery into healthcare systems and highlights the need for policy changes that support midwives in their practice. By empowering midwives and promoting their essential role in maternal and neonatal care, we can improve health outcomes for women and their newborns, fostering healthier families and communities.